The Analysis of Grammatical Errors in Speaking Activities Produced by Students at English Class Vocational High School of Yadika Lubuklinggau - Herlina Herlina (Channing : Journal of English Language Education and Literature, 2017)
The aimed of this study was to observe the grammatical errors in speaking activities produced by students at English class Vocational High School of YADIKA Lubuklinggau. It focused on (1) What is the most common type of students errors produced in speaking activities?; and (2) How is the proportion of students errors produced in speaking activities?. The writer employed descriptive method as the design of the study. The findings of this study showed that the students produced grammatical errors based on the surface strategy taxonomy which are classified into omission, addition, misformation and misordering. The result found that the most common type of errors produced in speaking activities was misformation errors because it occurred more than 50% of all type errors. The most frequent types were misformation errors occurred 145 items (60,87%), omission errors occurred 56 items (27,80%), addition errors occurred 19 items (8,51%) and misordering errors occurred only 5 items (2,82%).